EARLY PREDICTION AND EMERGING BIOMARKERS OF GESTATIONAL DIABETES MELITUS: A REVIEW - V. P. Rama Durga; N. Krishna Prabha (The Bioscan, 2026)
Gestational Diabetes Mellitus (GDM) is a metabolic disorder occurring during pregnancy, often associated with various complications for the mother and the baby. Complications of GDM include pre-eclampsia, foetal macrosomia, neonatal hypoglycemia, and the risk of developing type 2 diabetes. Conventional screening for GDM, i.e., the oral glucose tolerance test performed between 24 and 28 weeks of gestation, detects GDM relatively late. However, the recent studies have emphasised the search for new biomarkers for the early detection of GDM. Such markers would enable the application of preventive measures for the complications of GDM.